Public and private institutional arrangements for early generation seed production: Cassava seed value chains in Southeast Asia - Delaquis, E.; Almekinders, Conny J.M.; Haan, Stef de; Newby, J.C.; Thuy, C.T.L.; Srean, P.; Wannarat, W.; Aiemnaka, P.; Rojanaridpiched, C.; Nhan, P.T.; Kang, P.; Struik, P.C. (Elsevier, 2024)
CONTEXT Early generation seed (EGS) production and delivery pathways are critical components of so-called formal seed systems, of principal importance in the release of improved varieties into national seed systems. Vegetatively propagated crops (VPCs), with clonal reproductive ability and considerable differences in production and dissemination patterns from sexually propagated crops, often challenge generalized assumptions about ‘business models’ for private sector-led EGS production.